Wisata di tengah Pandemi COVID-19: Melihat respon masyarakat setelah Satu tahun Pandemi Covid-19 - Busro Busro (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
This study aims to look at the public sentiment represented by Twitter users regarding tourism during the COVID-19 pandemic. Data is taken using Drone Emprit Academic in the form of archives or written documents, images, or video recordings that are produced, distributed and responded to by Twitter social media users. The results showed that people did not pay more attention to tourism during the pandemic. The developing narrative related to the topic of tourism during a pandemic is an appeal and an invitation to follow health protocols from government accounts, namely the police and local governments. In addition, people still have a fear of doing tourism activities during a pandemic even though the pandemic has hit for one year.